Ionic conduction in ammonia functionalised closo-dodecaborates MB12H11NH3 (M = Li and Na) - Jensen,Steffen R.H.; Jørgensen, M.; Nguyen, Thi Phuong Thao; Nolan, Greg; Buckley, Craig E.; Jensen, T.R.; Paskevicius, Mark (2024)
Metal hydroborates and their derivatives have been receiving attention as potential solid-state ion conductors for battery applications owing to their impressive electrochemical and mechanical characteristics. However, to date only a fraction of these compounds has been investigated as solid-state electrolytes. Here, MB12H11NH3 (M = Li and Na) hydroborates are synthesized and investigated as electrolyte materials for all-solid-state batteries. The room temperature α-NaB12H11NH3 was structurally solved in P212121 (a = 7.1972(3) Å, b = 9.9225(4) Å, and c = 14.5556(5) Å). It shows a polymorphic structural transition near 140 °C to cubic Fm3̄m. LiB12H11NH3 and NaB12H11NH3 exhibit cationic conductivities of σ(Li+) = 3.0 × 10−4 S cm−1 and σ(Na+) = 1.2 × 10−4 S cm−1 at 200 °C. Hydration is found to improve ionic conductivity of the hydroborates. It is presumed that modest ionic conductivities could be due to a lack of significant re-orientational dynamics in the crystal structure resulting from the presence of the bulky -NH3 group in the anion.